THE DIFFERENCE BETWEEN RECITING THE QURAN WHILE WORKING AND WORK FATIGUE AMONG FEMALE NURSES AT MALAHAYATI ISLAMIC HOSPITAL AND HAJI MEDAN GENERAL HOSPITAL - Zahrani Nabilah; Putra Apriadi Siregar; Tri Niswati Utami; Nurhayati Nurhayati; Abdul Karim Batubara (Pusat Studi Gender dan Anak, 2025)
The most common problem faced by healthcare workers, especially nurses, is work- related fatigue, which can lead to decreased work productivity and quality of care. This study aims to determine the differences in work fatigue levels among nurses who listen to the recitation of the Quran while working at Malahayati Islamic Hospital and Haji Medan General Hospital. This study uses a comparative design with a cross- sectional approach. The study population consists of 156 nurses at Malahayati Islamic Hospital and 362 nurses at Haji Medan General Hospital. The sample consisted of nurses from both hospitals selected through purposive sampling, totaling 60 respondents. Data were collected using the KAUPK2 questionnaire to measure work fatigue levels, and a Mann-Whitney statistical test was conducted to analyze differences between the two groups. The results of this study indicate a significant difference in work fatigue levels between nurses who were consistently given Quran recitation and those who were not consistently given Quran recitation, with nurses who were consistently given Quran recitation tending to have lower fatigue levels compared to those who were not consistently given Quran recitation, with a p-value of 0.013 (<0.05). The conclusion of this study is that Quran recitation can be an alternative intervention to reduce work fatigue levels among nurses. It is hoped that hospitals will consider incorporating Quran recitation as part of their efforts to improve the well-being of healthcare workers.